1982
DOI: 10.1007/bf01887605
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of exophytic gastrointestinal leiomyosarcoma

Abstract: Five cases of exophytic gastrointestinal leiomyosarcoma were evaluated by sonography. In 3 of the 5 cases, identification of intraluminal air or intestinal lumen in an eccentric location to the mass was helpful in recognizing the exophytic nature of the mass. Tumor necrosis was present in all of the masses and also in 1 case of hepatic metastasis. Recognition of the exophytic nature of the mass and the presence of tumor necrosis favor the diagnosis of leiomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Gastrointestinal leiomyosarcomas can be hyperechoic or hypoechoic. Echo-free spaces due to liquefactive necrosis are frequently seen, in such a case, an echogenic rim is demonstrable [7,8]. When a central cavity communicates with the intestinal lumen, acoustic shadows from the air in the cavity can be shown.…”
Section: Discussionmentioning
confidence: 95%
“…Gastrointestinal leiomyosarcomas can be hyperechoic or hypoechoic. Echo-free spaces due to liquefactive necrosis are frequently seen, in such a case, an echogenic rim is demonstrable [7,8]. When a central cavity communicates with the intestinal lumen, acoustic shadows from the air in the cavity can be shown.…”
Section: Discussionmentioning
confidence: 95%
“…One reason for such a large tumor in the case reported herein is the exophytic growth of the LMS. Smooth muscle-originating tumors of the gastrointestinal tract frequently extend transmurally thus obstructing the intestinal lumen ( 13 , 22 ), although, sometimes they bulge out of the serosa in an exophytic fashion ( 13 ). These tumors usually then lead to obstructive gastrointestinal symptoms, which could enable the owners to recognize symptoms of the tumors before they grow to an enormous size, except in cases where a tumor occurs in the cecum and is positioned in such a way that it does not limit the passage of intestinal contents ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The jejunum is one of the most commonly affected regions of the gastrointestinal tract affected by LMS ( 8 , 9 ). The jejunal muscularis propria is usually involved, and the tumors often grow into the bowel lumen, thus inducing obstructive gastrointestinal symptoms, such as the retention of intraluminal gas or fluid ( 10 13 ). Several retrospective studies have reported the clinical and morphological characteristics, diagnosis, and prognosis of canine intestinal LMS ( 14 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most probable diagnosis was gastric leiomyoma or leiomyosarcoma, with necrotic areas explaining the existence of the cystic zones detected by ultrasonography. [6][7][8] The existence of an aberrant pancreas was a surprise finding, given its size and the sonographic appearance. This case clearly shows the value of ultrasonography undertaken with fluid filling the gastric cavity in the diagnosis of pathological conditions of the stomach.…”
Section: Discussionmentioning
confidence: 99%